Characterization of polysaccharide from longan pulp as the macrophage stimulator. Issue 118 (12th November 2015) - Yi, Yang; Wang, Hongxun; Zhang, Ruifen; Min, Ting; Huang, Fei; Liu, Lei; Zhang, Mingwei
Abstract : A 44.7-kDa polysaccharide LPIIa from longan pulp was mainly composed of →6)-Glc-(1→, →5)-Ara-(1→, →4)-Man-(1→ and →6)-Gal-(1→. It stimulated macrophage activation partly via TLR4 and TLR2, followed by p38 MAPK- and NF-κB-dependent signaling pathways. Abstract : Longan is one of the most popular subtropical fruits in Southeast Asia, because of its flavor and benefits to health. As one of the important active ingredients of longan pulp, polysaccharide LPIIa was obtained by hot water extraction, ion-exchange chromatography and gel filtration chromatography. Its physicochemical characterization and immunostimulatory effects on macrophages were then investigated. Structural analyses indicated that LPIIa was a 44.7 kDa heteropolysaccharide mainly composed of →6)-Glc-(1→, →5)-Ara-(1→, →4)-Man-(1→ and →6)-Gal-(1→. It enhanced macrophage phagocytosis and nitric oxide production in the dose range of 100–400 μg mL −1 . Moreover, it significantly increased the inducible nitric oxide synthase activity, tumor necrosis factor-α and interleukin-6 secretion of macrophages at 200 μg mL −1 . However, these effects were obviously weakened after toll-like receptor 4 (TLR4) or TLR2 was blocked. Likewise, the specific inhibitors of p38 mitogen-activated protein kinase (MAPK), protein kinase C, phosphatidylinositol 3-kinase, protein tyrosine kinase and nuclear factor κB (NF-κB) selectively depressed the immunostimulatory activities of LPIIa on macrophages. LPIIa stimulated macrophage activation partly via TLR4 and TLR2, followed by p38 MAPK- and NF-κB-dependent signaling pathways. The results suggested that LPIIa possessed potent immunomodulatory activity by stimulating macrophages and could be used as an immunotherapeutic adjuvant.